THE EFFECT OF LYSOPHOSPHATIDIC ACID ON THE COMPOSITION OF MYOSIN-9 AND TROPOMYOSIN CONTAINING CYTOPLASMIC PROTEIN COMPLEXES - Bobkov, D E; Kropacheva, I V (T͡S︡itologii͡a, 2017)
In this paper we investigate the distribution of myosin-9 in the cytoplasm of human embryonic lung fibroblasts. Using immunofluorescence, immunoprecipitation and western blotting, we demonstrated that myosin-9 forms multimolecular complexes with high molecular weight tropomyosin isoforms and actin in cytoplasm of cultured cells. We explored the levels of myosin-9, tropomyosin and actin in cytosol and cytomatrix extracts at different time points after LPA addition (20 ng/ml) to culture medium. Cytosole extracts from human embryonic lung fibroblasts were subjected to co-immunoprecipitation assay with polyclonal antibodies specific to C-terminal peptide of human myosin-9, or with monoclonal antibodies recognizing high molecular weight tropomyosin isoforms. The cross-immunoprecipitation method revealed changes in the composition of myosin- 9/tropomyosin complexes under the action of LPA. We have observed the significant decrease in myosin-9 co-immunoprecipitated tropomyosin level immediately (1 min) after LPA addition. Additionally, we have found that LPA treatment during 1 h induces proteolytic degradation of myosin-9 with accumulation of 130 kDa and 40 kDa fragments in cytomatrix fraction. These results suggest that cytoplasmic multimolecular protein complexes containing myosin-9 and tropomyosin are involved in the regulation of cellular response to LPA.